Analysis of Song Structure and Chord Progression in The Girl From Ipanema - Gabriel Albet Karuniawan (Repertoar, 2026)
This study aims to analyze the song form and chord progression of "The Girl From Ipanema" by Antonio Carlos Jobim and Vinicius de Moraes. This study uses a descriptive qualitative method, with data collected through interviews, observation, and documentation. The results of the study show that: (1) The Girl from Ipanema has a 3-part song form, namely A-B-A, in which a sequence technique is found in the development of the motif in each part. (2) This song is played in the key of F Major, with the following chord progression. In the introduction section, there is a progression of I9-IVm6-I9. In section A, there is a chord progression of IM9-IIm13-IIm7-IIb7#11-IM7, in section B, there is a progression of IM7-IV9-Im7-VI#9-I#m7-VI9 (in the key of F#) - IIIm7-VI(b9)-IIm7-V(b9) (in the key of F Major).